Level Of Staff Compliance with Procedures Information Security in Management Electronic Medical Records (ELMR) at Annisa Hospital, Bogor - Ferawati, Ferawati; Lestari, Winda Dwi; Fadilah, Rahma Sari (JURNAL KESEHATAN STIKes MUHAMMADIYAH CIAMIS, 2024)
Staff compliance is a crucial factor in maintaining the confidentiality, integrity, and availability of patient data, in line with the Minister of Health Regulation No. 269/2008 and the ITE Law No. 11/2008. EMR also increases the risk of sensitive patient data leakage if not managed with strict security procedures. Annisa Hospital Bogor, as an institution that has implemented EMR, is obliged to ensure the confidentiality, integrity, and availability of data. This study aims to measure and analyze the level of compliance of medical and non-medical staff at Annisa Hospital Bogor with information security procedures in managing Electronic Medical Records (EMDR). The method used is descriptive quantitative by distributing questionnaires to the EMR user staff population. The results showed that the average compliance rate was 81.6%, but vulnerabilities were found in the use of passwords and log-out protocols after accessing the system. The study recommends the need for regular training and systematic audits to improve staff awareness and discipline.